Integrasi Modul RF 2,4 GHz Pada Sistem Minimum ATmega328P dan Analisis Performa Komunikasi - Yulanda, Erik Agustian; Junia, Dea (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Low-power wireless communication has become increasingly essential in small-scale control and monitoring systems, especially in microcontroller-based devices that require minimal energy consumption while maintaining adequate range and reliability. The ATmega328P microcontroller is widely used in embedded applications; however, its standard configuration does not provide built-in Radio Frequency (RF) communication capabilities. This limitation necessitates the development of a minimum system capable of supporting efficient short-range wireless communication. To address this need, a 2.4 GHz nRF24L01 RF module was integrated into an ATmega328P minimum system, accompanied by the design of a power regulation circuit, an FTDI programming interface, and communication pathways compatible with various sensors. Performance evaluation was carried out through range testing, transmission stability assessment, data-transfer latency measurement, and power-consumption analysis under both indoor and outdoor conditions with variations in distance and physical obstructions. The results indicate that communication remained stable at distances of 5–15 meters indoors and 1–20 meters outdoors, with an average latency of 271.1 ms. Power consumption ranged from 14.2 to 31.8 mA, depending on the mode of operation. The integration of the RF module successfully enhances the communication capability of the ATmega328P and provides a strong foundation for the development of IoT devices and short-range automation systems.